2014
DOI: 10.1002/icd.1889
|View full text |Cite
|
Sign up to set email alerts
|

Children's Earliest Experiences with Death: Circumstances, Conversations, Explanations, and Parental Satisfaction

Abstract: Parents (n = 140) of children 2 to 7 years responded to an online survey regarding their children's experiences and conversations about death. A total of 75% of parents indicated that they had spoken to their child about death, and the majority of conversations were first initiated when children were between 3 and 3.5 years of age. Binary logistic regression analysis was used to explore factors that could predict conversations about death. Parents (n = 88) provided narratives of the explanations of death that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 35 publications
3
45
0
Order By: Relevance
“…Similar to the finding by Renaud et al (), the parents in Puebla reported that many of their children asked questions about death. Many of the questions concerned with día de los muertos focused on the meaning of various symbols related to the event.…”
Section: Discussionsupporting
confidence: 80%
“…Similar to the finding by Renaud et al (), the parents in Puebla reported that many of their children asked questions about death. Many of the questions concerned with día de los muertos focused on the meaning of various symbols related to the event.…”
Section: Discussionsupporting
confidence: 80%
“…Sixty-seven per cent of the parents reported that their children had asked questions about a death portrayed in the media, most commonly in books and films. Similarly, Renauld et al [27] found that a majority of parents they surveyed reported that their children were first exposed to death in the media. These parents also reported that their earliest conversations with children about death were most commonly about a media portrayal, followed by death of a pet and death of grandparents [27].…”
Section: Media Portrayals Of Death and Dyingmentioning
confidence: 94%
“…B 373: 20170267 these sorts of explanations. For example, Renaud et al [27] surveyed Canadian parents of 2-to 5-year-old children about their conversations about death and what these conversations included. Seventy-five percent of parents reported that they had spoken at least once to their child about death.…”
Section: Parental Communication About Death and Dyingmentioning
confidence: 99%
“…As children acquire more domain knowledge, their ability to ask questions improves and they ask more focused questions to fill specific knowledge gaps (Ronfard, Zambrana, Hermansen, & Kelemen, 2018). Many parents say that their children begin asking questions about death as young as age 3 (Renaud, Engarhos, Schleifer, & Talwar, 2015) and that the questions are often sparked by a recent death in the family (Bridgewater, Menendez, & Rosengren, 2019), so asking questions might also be a way children learn about death.…”
Section: Parental Conversations and Questionsmentioning
confidence: 99%